ANTIBIOTIC-ASSOCIATED DIARRHEA. PROBLEMS AND SOLUTIONS CONTINUOUS PROFESSIONAL EDUCATION - O.I. Nyrkova; M.K. Bekhtereva; A.S. Kvetnaya; L.I. Zhelezova ("Paediatrician" Publishers LLC, 2011)
In a literature survey we have enlightened modern conceptions of antibiotic-associated diarrhea genesis, peculiarities of a clinical course of the disease depending on the etiology, main diagnostic principles and treatment approaches. Author's objective was to attract attention of medical professionals from all specialties to this problem. Key words: antibiotic-associated diarrhea, Clostridium difficile, diagnostics, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 54-62.)